Does stereotactic body radiation improve outcomes compared to conventional radiation for liver cancer patients?. (July 2022) - Lock, Michael; Chow, Ronald; Jayatilaka, Aruni; Plotnick, Meghan; Stephens, Robert; Nguyen, Timothy; Fisher, Barbara; Wong, Eugene; Gaede, Stewart
Highlights: There has been a paradigm shift to SBRT without evidence that these high-dose ultra-low fractions result in improved outcomes. This prospective cohort compares the survival of patients treated with conventional versus SBRT treatments for liver tumours. The SBRT group received an average of 5 fractions, and the conventional group received an average of 17 fractions. 397 patients were included. Overall survival was higher for SBRT patients at the 2-year time point (42% vs 27% p = 0.01). Abstract: Introduction: Over the past decade, there has been a paradigm shift to higher doses per fraction of liver stereotactic body radiotherapy (SBRT). However, this shift may not be due to evidence alone, but rather result of convenience and remuneration. This prospective cohort study aims to compare outcomes of patients who received moderately hypofractionated and hypofractionated radiotherapy treatments for liver tumours. Methods: Patients treated for liver cancer with radiotherapy between 2004 and 2020 were prospectively entered in this study. Patients were stratified into two groups: hypofractionation group of patients receiving an average of 5 fractions, and moderate hypofractionation group of patients receiving an average of 17 fractions. Other components of precision radiotherapy such as image guidance were the same between groups. The primary outcome was 2-year overall survival. The secondary outcomes were (1) change in toxicity as assessed by the Radiation Therapy Oncology Group (RTOG) toxicity criteria from baseline to 3 months, and from baseline to 6 months; and (2) change in Child Pugh score from baseline to 3 months. Type I error was prespecified at 0.05. Results: 397 patients were included. A larger proportion of patients on hypofractionated regimens were alive at the 2-year time point, relative to those who received moderately hypofractionated regimens (42% vs 27% p = 0.010); no difference was noted at the 1-year time point. Mean toxicity change in RTOG symptoms from baseline to 3 and 6 months, and in Child Pugh score from baseline to 3 months, were not statistically different between the two groups. Conclusion: When compared to conventional radiation fractionation, liver SBRT tends to be associated with a significant overall survival benefit, justifying a randomized trial to confirm. The concern that the trend to higher dose per fraction may result in increased toxicity, specifically in the treatment of high-risk liver patients, appears to be unfounded. The hypofractionated component of SBRT may be the critical dosimetric factor impacting on survival.